Reorientation of Islamic Education: Synergizing Tarbiyah and Dakwah to Answer Social Problems - Abdullah, Mukhammad (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2018)
Islamic education is often claimed to fail in improving the character of the nation. This is due to the increasing number of social cases that occur and all of them are rooted in the decline of moral quality and character of the nation. In fact, there are still many Islamic education institutions that emphasize their tarbiyah aspects without compensating for the quality of their preaching. Whereas Islamic scholarship in nature does not recognize the existence of scientific dichotomy, as is the majority of western scientific products. Muslim thinkers themselves have offered many concepts of scientific integration, such as the thariqah al-ankabut theory of Amin Abdullah. This article aims to explore the reorientation of Islamic education to synergize the aspects of tarbiyah and da'wah as an alternative answer to various social problems. This article used a qualitative library research with the hope that a more comprehensive synthesis of thought will be produced on how important the reorientation of Islamic education is. This article concludes that social problems must be overcome from the root, namely the quality of faith that manifests in character in community life. Therefore, Islamic education must be integrative, so there must be harmonious synergy between tarbiyah orientation and da'wah. This is so that the output of Islamic education is truly capable of animating and authenticating the unity of Islamic scholarship which is integrated in all aspects of life. Good cooperation is needed among all stakeholders to realize the reorientation of Islamic education, due to the increasing diversity of social problems.